2015
DOI: 10.1371/journal.pone.0131538
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Particulate Organic Carbon Export at Eddy Edges in the Oligotrophic Western North Pacific Ocean

Abstract: Mesoscale eddies in the subtropical oligotrophic ocean are ubiquitous and play an important role in nutrient supply and oceanic primary production. However, it is still unclear whether these mesoscale eddies can efficiently transfer CO2 from the atmosphere to deep waters via biological pump because of the sampling difficulty due to their transient nature. In 2007, particulate organic carbon (POC) fluxes, measured below the euphotic zone at the edge of warm eddy were 136–194 mg-C m−2 d−1 which was greatly eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 46 publications
8
40
1
Order By: Relevance
“…Moreover, POC fluxes for this ACME were also in line with estimates made for other eddies, such as enhanced POC fluxes determined at the rim of a CE in the Western Pacific (Shih et al, 2015) or inside a CE in the ETNA (Fig. 8, derived from aOUR data in Karstensen et al, 2015).…”
Section: Oxygen Utilization and Carbon Exportsupporting
confidence: 86%
“…Moreover, POC fluxes for this ACME were also in line with estimates made for other eddies, such as enhanced POC fluxes determined at the rim of a CE in the Western Pacific (Shih et al, 2015) or inside a CE in the ETNA (Fig. 8, derived from aOUR data in Karstensen et al, 2015).…”
Section: Oxygen Utilization and Carbon Exportsupporting
confidence: 86%
“…At stations I1 and I2, the euphotic zone depth was relatively shallow (∼ 70 m), with more light attenuation from suspended particles, which could be caused by elevated particle production. This finding corresponds to the station locations at the edge of the anticyclonic eddy where particulate organic carbon (POC) fluxes can be 2-4-fold higher than those in adjacent oligotrophic waters (Zhou et al, 2013;Shih et al, 2015). For station I4, the case was similar to I1 and I2, as it was located at the edge of two large anticyclonic eddies (supplement).…”
Section: The Response Of Coccolithophores To Eddies In the South Chinsupporting
confidence: 67%
“…For example, different environmental provinces can shift from a community dominated by normally calcified E. huxleyi type A to one characterized by weakly calcified B/C on the Patagonian Shelf and in the Southern Ocean (Cubillos et al, 2007;Poulton et al, 2011). More heavily calcified morphotypes during low C in winter may be responsible for the seasonal morphotype transition in the Bay of Biscay (Smith et al, 2012). Seasonal variability of E. huxleyi coccolith size has also been observed in the Aegean Sea, which may be due to genotypic or ecophenotypic variation (Triantaphyllou et al, 2010).…”
Section: Carbonate Chemistrymentioning
confidence: 99%
“…The magnitude of the increases in total lipid and phytoplankton‐derived lipid fluxes following Nicole is of the same magnitude as the increases in labile lipid fluxes that have been observed at 3,200 m depth at the Bermuda Time Series Site following mesoscale physical forcing of a transient bloom (Conte et al, , ; Table S1). Previous studies have demonstrated that mesoscale ocean features can stimulate production and carbon export to the deep ocean (Conte et al, ; Pedrosa‐Pàmies et al, ; Shih et al, ; Stukel et al, ), but the only prior documented evidence of storm‐induced export of POC to depth is the study of Chen et al () in the oligotrophic northwest Pacific Ocean, where an increase in flux of POC at 125 m depth was observed following an extreme weather event.…”
Section: Discussionmentioning
confidence: 99%